Pengaruh Pelatihan, Motivasi, dan Prestasi Belajar terhadap Kesiapan Kerja - Sharla Annisa Putri; Khoirul Attiq; Syifa Rohmah (CV. Denasya Smart Publisher, 2025)
The purpose of this study was to determine the effect of on the job training, work motivation, and learning achievement on work readiness. The research method used is quantitative with statistical analysis. The research population included 12 state vocational schools in Purbalingga Regency. This study used a sample of 100 students selected through purposive sampling technique with the criteria of 12th grade students, and had attended training, the formula used in this study was the slovin formula. The data taken using an online questionnaire, data processing using IBM Statistics SPSS software version 24. The results of this study indicate that: (1) On The Job Training (X1) has a significant positive effect on work readiness (Y), (2) Work Motivation (X2) has no effect on work readiness (Y), (3) Learning Achievement (Y) has a significant positive effect on work readiness (Y). For future researchers, it is recommended to consider other factors that can affect work readiness and future researchers can expand the research sample so that the research results can be generalized.